Effect of ROA, EPS, dan NPM on the Stock Price of Property And Real Estate Sub-Sector Companies in 2009-2018 - Maulidatul Hasanah; Emma Suryani (PT Larva Wijaya Penerbit, 2022)
This study was conducted to determine how much influence the ratio of ROA, EPS, and NPM to the stock price of the property and real estate sub-sector companies. The research population is property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2009-2018 as many as 34 companies. The research sample amounted to 28 companies which were taken using purposive sampling method. This research uses causal research. The data analysis technique used in this research is multiple linear regression analysis. Based on the results obtained from the study showed that: 1). ROA partially has a negative and significant effect on stock prices, 2). EPS partially has a positive and significant effect on stock prices, 3). NPM partially has no significant effect on company stock prices